Trends of Acupuncture Therapy on Depression From 2011 to 2020: A Bibliometric Analysis - Xiang, Hongchun; Li, Jing; Li, Bocun; Tan, Qian; Cai, Guowei (Frontiers in Psychology, 2021)
Objectives: The purpose of this study was to explore the current status and trends of acupuncture for depression in the last decade and provide new insights for researchers in future studies. Methods: Articles regarding acupuncture treatment for depression published between 2011 and 2020 were extracted from the Web of Science Core Collection. We used CiteSpace to analyze data on publications, countries, institutions, cited journals, cited authors, cited references, keywords and citation bursts about acupuncture and depression. Results: A total of 1032 publications were obtained from 2011 to 2020. We identified the most prolific journals, countries, institutions, and authors in the field of acupuncture for depression in the last decade. The most prolific country and institution were the People's Republic of China and KyungHee University, respectively. The Evidence-based Complementary and Alternative Medicine was the most prolific journal, and cited journal. The author with the highest centrality was Zhangjin Zhang, and the author with the most publications was Park Hi-Joon. The keyword of “cognitive behavioral therapy” was first for research developments with the highest citation burst. The five hot topics in acupuncture on depression were “acupuncture”, “depression”, “electro-acupuncture”, “quality of life” and “anxiety”. Conclusions: The results from this bibliometric study provide insight into research trends in acupuncture therapy for depression, and current status and trends during the past decade, which may help researchers determine the current status, hot spots, and frontier trends in this field.